2014
DOI: 10.1177/156482651403500214
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Management of Acute Malnutrition in Bangladesh: Feasibility and Constraints

Abstract: Background. To achieve the United Nations Millennium Development Goals, particularly reduction in child mortality (Millennium Development Goal 4)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
0
14
0
1
Order By: Relevance
“…Quote: "The populations studied were mostly elderly including those with hip fractures, pressure ulcers, chronic obstructive pulmonary disease (COPD), cancer, gastro‐intestinal disease, and a range of critical and acute illnesses. "Choudhury 2014Methods: no details on screening; no 'Risk of bias' assessmentCollins 2015Methods: no mention that data extraction performed in duplicate. Participants: adult inpatients in rehabilitation, geriatric evaluation medicine wards or similarCoyne‐Meyers 2004Methods: did not report methods; no 'Risk of bias' assessmentDaniels 2010Methods: no 'Risk of bias' assessmentde van der Schueren 2016Methods: no 'Risk of bias' assessment; based on 2 previous reviewsDewey 2008Methods: search terms and databases not listed; no mention that screening or data extraction performed in duplicate.Elia 2016Methods: AMSTAR score of 5; no mention that data extraction or 'Risk of bias' assessment performed in duplicate, though stated Cochrane methods were used to assess risk of bias.Els 2013Methods: no mention that data extraction and 'Risk of bias' assessment performed in duplicate.Fatima 2015Methods: methods not describedFerreira 2010Methods: 2 databases searched; review methods not reportedGoudet 2017Methods: scoping reviewMethods: 1 reviewer screened; no 'Risk of bias' assessmentGrantham‐McGregor 2014Methods: no mention that screening or data extraction performed in duplicate; no 'Risk of bias' assessmentGresham 2014Methods: not described Intervention: 25 studies on macronutrients reported, combined with 6 studies on micronutrients.Gresham 2016Methods: second independent reviewer extracted data from half of the studies.Intervention: dietary intervention, macronutrients, micronutrients; data not reported separately; no information reported on intervention.Gunaratna 2010Methods: no mention that screening or data extraction performe...…”
Section: Resultsmentioning
confidence: 99%
“…Quote: "The populations studied were mostly elderly including those with hip fractures, pressure ulcers, chronic obstructive pulmonary disease (COPD), cancer, gastro‐intestinal disease, and a range of critical and acute illnesses. "Choudhury 2014Methods: no details on screening; no 'Risk of bias' assessmentCollins 2015Methods: no mention that data extraction performed in duplicate. Participants: adult inpatients in rehabilitation, geriatric evaluation medicine wards or similarCoyne‐Meyers 2004Methods: did not report methods; no 'Risk of bias' assessmentDaniels 2010Methods: no 'Risk of bias' assessmentde van der Schueren 2016Methods: no 'Risk of bias' assessment; based on 2 previous reviewsDewey 2008Methods: search terms and databases not listed; no mention that screening or data extraction performed in duplicate.Elia 2016Methods: AMSTAR score of 5; no mention that data extraction or 'Risk of bias' assessment performed in duplicate, though stated Cochrane methods were used to assess risk of bias.Els 2013Methods: no mention that data extraction and 'Risk of bias' assessment performed in duplicate.Fatima 2015Methods: methods not describedFerreira 2010Methods: 2 databases searched; review methods not reportedGoudet 2017Methods: scoping reviewMethods: 1 reviewer screened; no 'Risk of bias' assessmentGrantham‐McGregor 2014Methods: no mention that screening or data extraction performed in duplicate; no 'Risk of bias' assessmentGresham 2014Methods: not described Intervention: 25 studies on macronutrients reported, combined with 6 studies on micronutrients.Gresham 2016Methods: second independent reviewer extracted data from half of the studies.Intervention: dietary intervention, macronutrients, micronutrients; data not reported separately; no information reported on intervention.Gunaratna 2010Methods: no mention that screening or data extraction performe...…”
Section: Resultsmentioning
confidence: 99%
“…Programs need to ensure a strengthening of the health system [31] and integrate the use of these products with other public health interventions to ensure a continuum of care from prevention to treatment of MAM. These interventions have been described in detail in other papers of this Supplement [32] and include behavior change interventions and counseling on MAM treatment [33] and adequate infant and young child feeding practices, including interventions on promotion of breastfeeding and complementary feeding with adequate dietary diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to assess the readiness of the health system functionaries with regard to identification of malnourished children in the community, distribution of therapeutic foods, and follow up of the treated cases. Choudhury et al has reported the feasibilities and constraints of CMAM implementation in Bangladesh [ 16 ]. However, the article was essentially a desk review and did not systematically analyze the multiple dimensions of health system in the context of CMAM implementation [ 17 ].…”
Section: Introductionmentioning
confidence: 99%